Codon-Optimized Rhodotorula glutinis PAL Expressed in Escherichia coli With Enhanced Activities - Xue, Feiyan; Liu, Zihui; Yu, Yue; Wu, Yangjie; Jin, Yuxin; Yang, Mingfeng; Ma, Lanqing (Frontiers in Bioengineering and Biotechnology, 2021)
PAL (phenylalanine ammonia lyase) is important for secondary metabolite production in plants and microorganisms. There is broad interest in engineering PAL for its biocatalytic applications in industry, agriculture, and medicine. The production of quantities of high activity enzymes has been explored by gene cloning and heterogenous expression of the corresponding protein. Here, we cloned the cDNA of Rhodotorula glutinis PAL (RgPAL) and introduced codon optimization to improve protein expression in Escherichia coli and enzyme activities in vitro. The RgPAL gene was cloned by reverse transcription and named pal-wt. It had a full-length of 2,121 bp and encoded a 706 amino acid protein. The pal-wt was inefficiently expressed in E. coli, even when the expression host and physical conditions were optimized. Therefore, codon optimization was used to obtain the corresponding gene sequence, named pal-opt, in order to encode the same amino acid for the RgPAL protein. The recombinant protein encoded by pal-opt was successfully expressed in E. coli and then purified to detect its enzymatic activity in vitro. Consequently, 55.33±0.88 mg/L of RgPAL protein with a specific activity of 1,219±147 U/mg and Km value of 609 μM for substrate L-phenylalanine was easily obtained. The enzyme protein also displayed tyrosine ammonia lyase (TAL) specific activity of 80±2 U/mg and Km value of 13.3 μM for substrate L-Tyrosine. The bifunctional enzyme RgPAL/TAL encoded by an optimized gene (pal-opt) and its easy expression advantage will provide an important basis for further applications.